"These are our roots": the history of the K'iche' people as told by lords of the Tamub' and Ilokab' - Christenson, Allen J., translator; University Press of Colorado, publisher (Colorado State University. Libraries, 2026)
This book translates and analyzes historical documents composed by Tamub' and Ilokab' nobles of the K'iche' Maya in 16th-century Guatemala, providing alternative perspectives to Kaweq lineage writings through indigenous texts.--Provided by publisher.
These are our roots: the history of the K'iche' people as told by lords of the Tamub' and Ilokab'
The Tamub' and Ilokab' people -- Highland Maya land titles -- Christianity, accommodation, and resistance -- History of the Tamub' and the Ilokab' -- The poetic structure of the Titles of the Tamub' and Ilokab' -- Orthography -- History of the K'iche' by Don Juan de Torres (Tamub' I) -- English translation -- Literal English translation with parallel K'iche' text in modern orthography -- K'iche' text with original sixteenth-century orthography -- The Title of Cristóal Ramírez (Tamub' II) -- English translation -- Partial transcription of the sixteenth-century Spanish manuscript -- Title of Pedro Velasco (Tamub' III) -- English translation -- Literal English translation with parallel K'iche' text in modern orthography -- K'iche' text with original sixteenth-century orthography -- Title of the Ilokab' -- English translation -- Literal English translation with parallel K'iche' text in modern orthography -- K'iche' text with original sixteenth-century orthography -- Genealogy of the Tamub' and Ilokab' lineages.
Keywords: Historia Quiché de D. Juan de Torres. Quiché; Título de Cristóóbal Ramírez. Quiché; Título de Pedro Velasco. Quiché; Título de los Ilokab. Quiché; Quiché Indians; Quiché Indians -- History; Quiché Indians -- Government relations